Optimalisasi Peran Humas Sekretariat DPRD Kabupaten Bogor dalam Meningkatkan Transparansi Lembaga melalui Pemanfaatan Media Sosial - Muhamad Aldi Fadli; Ahmad Musyarofi; Muhammad Rafli; Ahmad Rizky Nur Razab4; Mu'arif SAM (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
This study examines the urgency of institutional transparency in the Secretariat of the Bogor Regency Regional People's Representative Council (DPRD) amid demands for good governance. The objective is to analyze the strategic role of the Public Relations, Protocol, and Publication Team of the Bogor Regency DPRD Secretariat in disseminating public information, with a focus on the use of the @setwankabbogor Instagram account as an instrument of transparency. Using a qualitative approach with a case study design, this research applies qualitative content analysis and observation of Instagram accounts, supported by organizational documentation related to the main tasks of Public Relations. The communication practices found were analyzed based on the theoretical benchmarks of the Two-Way Symmetrical Model and Organizational-Public Dialogic Communication (OPDC). Preliminary research results show that although Public Relations has been effective in documenting protocol and routine administrative activities, content related to core legislative functions such as the budget (KUA/PPAS) and oversight tends to be less dominant than ceremonial posts. The communication model applied still leans toward the Public Information Model, rather than the optimal Two-Way Symmetrical Model. Analysis shows a deficit in dialogic elements, particularly in genuine responsiveness (mutuality) and proactivity in discussing complex public issues, which has the potential to hinder the development of public trust. Optimization requires a shift in strategy towards evidence-based content planning and a focus on proactive dialogue and responsiveness, supported by institutional commitment and increased human resource capacity.